SIPDA SMA Negeri 4 Medan: The Development of Integrated Online Learning Platform - Lubis, M. Joharis; Lubis, Malan; Naelofaria, Salmah (Budapest International Research and Critics University, 2021)
The education units experienced several problems in online learning during this pandemic including the senior high school of SMA Negeri 4 Medan. Therefore, this research intends to produce a Moodle-based online learning platform that will be used by the teachers and the students at SMA Negeri 4 Medan. This article is a part of a research and development activity. Through this article, the process of developing sipdasma4medan would be explained. This study used a descriptive method. Based on the development process, the stages of making sipdasma4medan include: 1) downloading and installing Moodle after fulfilling several technical requirements, they are: (a) Web servers such as LiteSpeed and database program such as MariaDB. (b) PHP that has been configured and the required extensions, (c) Sendmail if it requires access to use an email. 2) creating databased, 3) creating directories, 4) installing moodle, 5) setting up cron, 6) setting up subjects in moodle. Furthermore, the sipdasma4medan.com product was validated by a design expert to assess the quality of the online learning platform that had been produced. The results of the expert validation show that sipdasma4medan functioned well, as indicated by the presentation results of assessment data through beta testing on e-learning. It was obtained 94.11% which means that sipdasma4medan as an online learning platform is very feasible to use.